Adoption of Contraceptive Methods among Eligible Couples in a Rural Area of Mymensingh District, Bangladesh (Community Based Medical Journal, 2025)
Contraceptive prevalence influences fertility which in turn influences socioeconomic growth, health care especially maternal and child health (MCH) care and quality of life. This cross-sectional, descriptive study was conducted in Churkhai village under Mymensingh district, Bangladesh, between December 2021 and April 2022, to estimate the prevalence of adoption of different contraceptive methods among eligible couples. Study population was eligible couples of a rural area. Purposively selected sample size was 180. Data were collected on a predesigned questionnaire by direct interviewing women of reproductive age group. Data entry was done in an MS-Excel sheet and analysis was done by SPSS version 20.0. Age of respondents ranged from 17 years to 49 years.  The mean age was 28.90±7.70 years. The majority of respondents (96.67%) were housewives and 21.11% respondents were illiterate. We found that contraceptive prevalence among eligible couples was 85%, while total fertility rate (TFR) was 2.2. Contraceptive prevalence was more (63.33%) among female respondents in comparison to male (21.67%). Contraceptive prevalence was influenced by participants’ age (highest between 25 and 34 years), religion and caste (100 percent among Hindus), occupation (100 percent among service holders and business professionals), socioeconomic condition and female literacy. Adoption of different methods included oral contraceptive pill (OCP) (50%), hormone injection (8.89%), intrauterine contraceptive device (IUCD) (1.11%), hormonal implant (1.11%), tubal ligation (2.22%), male condom (21.11%) and non-scalpel vasectomy (NSV) (0.56%). Temporary methods (82.22%) were much more accepted than that of permanent methods (2.78%). Our data suggests that using contraceptives for spacing method is much more popular than that of long acting and permanent methods among eligible couples. Contraceptive and reproductive education and better socio-economic condition can play an important role in use of contraceptive methods.  CBMJ 2025 January: Vol. 14 No. 01 P: 28-33